Capacities and Limitations of Wind Tunnel Physical Experiments on Motion and Dispersion of Different Density Gas Pollutants - Zavila Ondřej; Blejchař Tomáš (Measurement Science Review, 2017)
The article focuses on the analysis of the possibilities to model motion and dispersion of plumes of different density gas pollutants in lowspeed wind tunnels based on the application of physical similarity criteria, in this case the Froude number. The analysis of the physical nature of the modeled process by the Froude number is focused on the influence of air flow velocity, gas pollutant density and model scale. This gives an idea of limitations for this type of physical experiments in relation to the modeled real phenomena. The resulting statements and logical links are exemplified by a CFD numerical simulation of a given task calculated in ANSYS Fluent software.